2014
DOI: 10.1088/0031-8949/89/5/054017
|View full text |Cite
|
Sign up to set email alerts
|

The negative parity bands in156Gd

Abstract: The high flux reactor of the Institut Laue-Langevin is the world most intense neutron source for research. Using the ultra highresolution crystal spectrometers GAMS installed at the in-pile target position H6/H7 it is possible to measure nuclear state lifetimes using the Gamma Ray Induced Recoil (GRID) technique. In bent crystal mode, the spectrometers allow to perform spectroscopy with a dynamic range of up to six orders magnitude. At a very well collimated external neutron beam it is possible to install a hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The latter comes from the analysis of the negative-parity spectrum in 156 Gd, measured in the ILL laboratory in a series of experiments using the Bragg spectrometry methods, (see, Ref. [2]). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter comes from the analysis of the negative-parity spectrum in 156 Gd, measured in the ILL laboratory in a series of experiments using the Bragg spectrometry methods, (see, Ref. [2]). …”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we apply a harmonic-like model, discussed in details in Ref. [1], to reproduce the experimental B(E1) and B(E2) probabilities in 156 Gd, a nucleus supposed to possess low-lying tetrahedral, negative-parity band and for which some data of interest are available from the recent experiments [2,3]. We thus analyze the behaviour of the electric transition probabilities within and between the ground-state and the negative-parity bands in order to find out to which irreducible representation of the tetrahedral group T d (or the octahedral group O) the state of interest could belong.…”
Section: Introductionmentioning
confidence: 99%
“…Predictions of the possible presence of tetrahedral symmetry [1][2][3][4] at low spins and excitation energy in nuclear spectra have prompted several experimental studies [5][6][7] in the Z ≈ 64 and N ≈ 90 region. These nucleon numbers are considered to be magic with respect to this tetrahedral symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…In Refs. [3,7], it has been suggested that tetrahedral vibrational bands would have negative parity with K π = 2 − and a transition strength ratio of the inband E2 over the interband E1 decays, B(E2)/B(E1), an order of magnitude greater than for octupole vibrational bands. The current work focuses on interpreting the low-spin, negative-parity states in 156 Dy, as well as on extending the negative-parity, quasiparticle structures.…”
Section: Introductionmentioning
confidence: 99%